Enzymeless electrochemical detection of hydrogen peroxide using NiO octahedron decorated 3D graphene hydrogel - Mohamed A. Yassin; Ayman F. Abou-Hadid; Hamouda M. Mousa; Chan Hee Park; Cheol Sang Kim; Ali Salem; Mohamed A. Mattar (Scientific Reports)
Abstract Nowadays, electrochemical biosensors have gained extensive consensus to detect a wide variety of analytes such as hydrogen peroxide (H2O2), glucose, dopamine, uric acid, and so on. However, the detection of H2O2 is more and more important because H2O2 plays a vital role in our daily life. Hence, a new nonenzymatic H2O2 biosensor was developed by decorating NiO octahedrons on the 3-dimensional graphene hydrogel (3DGH). The NiO octahedrons were prepared using a mesoporous silica SBA-15 as a hard template. Then, different amounts of NiO octahedrons self-assembled with 3DGH during hydrothermal method. The performance of different prepared nanostructures as H2O2 biosensors electrodes was determined by the cyclic voltammetry and chronoamperometry tests. Various physicochemical methods such as FE-SEM, HR-TEM, XRD, TGA and Raman were utilized to characterize the morphology and structure properties of the as-prepared samples. The electrochemical sensing of H2O2 for the proposed biosensor electrodes are investigated, and the 3DGH/NiO nanocomposite electrode with NiO content of 25% displays high sensitivity with wide linear range and low detection limit, as well as good selectivity, reproducibility and long-term stability. Finally, the analytical utilities of the 3DGH/NiO25 proposed electrode were conducted to detect H2O2 in real products of milk samples.